Factors Related to the Incidence of Pesticide Toxicity in Pesticide Traders in Paser District in 2018 - Baini Rahman1, Eko Suhartono, Ardik Lahdimawan3, Husaini4, Lenie Marlinae5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pesticide sale circumstances in Paser District through measuring cholinesterase enzymes by the laboratory of the Paser District on the blood of pesticide traders found 37.5% experienced organopospat group pesticide toxicity. This research aim to analyze risk factors related to the level of pesticide toxicity in pesticide traders namely age, nutritional status, educational level, length of work, work period and use of personal protective equipment. The study design used was observational with a cross sectional approach. The number of samples is 42 people taken by simple random sampling. Measurement data using observation and examination sheetcholinesterase levels in the blood of respondents using Tintometer tool brands inScienPro Pest 100. The data were analyzed using Chi-square and multiple logistic regression. Pesticide traders who experienced pesticide toxicity were 42.9%. Result of Chi-Square test shows three variables that have a significant relationship with the incidence of pesticide toxicity. Risk factors for pesticide toxicity were age (p=0.021; OR=6.250; 95% CI=1.511-25.860), length of work (p=0.038; OR=6.769; 95% CI=1.268-36.139) and work period (p=0.043; OR=4.900; 95% CI=1.238-19.399). Multiple logistic regression showed that the most dominant factor associated with the incidence of pesticide toxicity namely the length of work and work period. Risk factors associated with the incidence of pesticide toxicity are age, length of work and work period where is the last two are the dominant factors.